Служба приватного сыска. Травля лисы - Константинов Андрей (Русский проект, 2002)
Экземпляры: Ф. 2 (20200710) / Инвентарный номер: 37414 / Цена: / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: К 65 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44